Case Report of a Rare Nonpuerperal Uterine Inversion Managed with Uterosacral Ligament Hysteropexy - Ali Azadi; Alexandra Wolfe; Greg J. Marchand (Hindawi Limited, 2021)
Nonpuerperal uterine inversions are rare. Typically occurring in older women, they are most commonly due to transcervical mass expulsion. Diagnosis is often difficult because of vague symptomatology, presentation, and unknown course of the pathology. Surgical correction is often necessary in the presence of active bleeding or prolapse severity causing urinary retention. This case of nonpuerperal inversion presented to the emergency department with vaginal bleeding and mass protrusion. The examination was consistent with POPQ stage IV prolapse and uterine inversion secondary to cervical expulsion of multiple uterine fibroids. Because of full cervical dilation and concerns of ureteral injury with an extirpative procedure, vaginal myomectomy was performed with concomitant robotic uterosacral ligament hysteropexy. The operative procedure and postoperative course were uncomplicated, and discharge occurred on post-op day 1. She remained asymptomatic at the 6-month follow-up encounter. Though uterine preservation has been performed in cases of uterine inversion to maintain fertility, there are no reported cases of concomitant hysteropexy being completed for correction of POPQ stage IV prolapse simultaneously encountered. Additionally, the novel robotic approach has not been documented. This case illustrates the short-term success of robotic uterosacral hysteropexy as an additional option of care with potentially less morbidity when compared to hysterectomy for advanced stage uterine prolapse with nonpuerperal uterine inversion.